Enhancement of the thermal, electrical properties and mechanical properties of graphene doped novel copolymers bearing coumarin side groups - Tanyildizi, Brahim; Macit, Cevher Kursat; Biryan, Fatih; Ozel, Cihan (Elsevier, 2025)
In this study, a new monomer 3-acetyl coumarin-7-ylacrylate (Ac-Kum) was synthesized. A series of copolymer were prepared by using (Ac-Kum) and methyl methacrylate (MMA) in different ratios. The structure characterization of the compounds was carried out by FT-IR, 1H NMR and 13C NMR spectroscopic techniques. Graphene doped polymer composites were prepared at different rates (1 %, 2 % and 5 %). The thermal behavior of the polymer composites were investigated by differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA) methods. Thermal stability of 1 %, 2 % and 5 % graphene composites of homopolymer was determined as 324 degrees C, 345 degrees C and 350 degrees C, respectively. The dielectric properties of the polymer composites were investigated as a function of frequency. Dielectric constant, dielectric loss and ac conductivity values of homopolymer were determined as 6.13, 0.11, 1.02 x 10- 09 S/cm and 5 % graphene composite were determined 49.30, 7259, 9.26 x 10- 07, respectively. Microhardness tests were carried out under a load of 100 g and in 10 s. The microhardness values were calculated by taking the average of the microhardness values taken from the surface of the samples from five different points. The highest microhardness value is the 5 % graphene added P (Ac-Kum) sample. Wear tests were carried out with a pin-on-disc wear tester under single load (10N) and in dry conditions with a total sliding distance of 10 m and a sliding speed of 5 mm/sec. Disc samples with a diameter of 13 mm were placed in the sample holder part of the test device. The highest wear resistance sample is the P(AcKum) 5 % graphene composite.
Keywords: Coumarin; Graphene; Composite; Mechanical properties; Electrical properties